Peningkatan Sadar Politik bagi Calon Legislatif Menjelang Pemilu dan Pemilukada Tahun 2024 di Provinsi Banten - Febri Saefulloh; Agung Tesa Gumilar; Titi Alawiyah; Kartika Delsya; Ria Erica Salty (Science and Education Journal (SICEDU), 2026)
The simultaneous general elections (Pemilu) and regional elections (Pemilukada) of 2024 in Banten Province present a clear democratic irony: the quantitative increase of legislative candidates from 85 to 100 seats has not been matched by a corresponding growth in their political awareness. This study aims to analyze the level of political awareness among legislative candidates (caleg) in Banten Province and the adaptive strategies they employ in response to structural challenges in the 2024 electoral contest. A qualitative approach utilizing a case study method was employed to explore this phenomenon in depth. Data were collected through in-depth interviews, participatory observation, and document analysis of 12 candidate informants from various political parties across the Millennial and Gen Z generations, selected through purposive sampling in Serang City, Banten Province. Data were analyzed using the Miles and Huberman interactive model, validated through source and technique triangulation. The findings reveal two dominant structural challenges: the hegemony of high cost politics that marginalizes intellectual capital, and a political awareness deficit at both the candidate and voter levels. Conversely, adaptive strategies were identified, including social media utilization as a low-cost campaign instrument, local wisdom approaches, and religious symbolism. This study concludes that enhancing political awareness requires a fundamental transformation in the role of political parties, from mere electoral vehicles to substantive political education institutions through structured and sustained mentoring and cadre development.